Pretreatment By Ceriporiopsis Subvesmispora And Phlebia Subserialis Of Wheat Straw And Its Impact On Subsequent Soda-Aq And Kraft-Aq Pulping - Ates, Saim; Ni, Yonghao; Atik, Celil; Imamoglu, Sami (Aperta, 2008)
Pretreatments of wheat straw with two different lignin-degrading fungal cultures Ceriporiopsis subvesmispora and Phlebia subserialis- were carried out and their effects on soda-AQ and kraff-AQ pulping were studied. After two weeks of bio-treatment of the wheat straw, both fungus were found to be suitable for bio-chemical pulping. The fungal pretreatment decreased the kappa number by as much as 24% and the unbleached pulp brightness increased by about 7% at a constant yield. Furthermore, the bio-pretreatment increased the brightness of the fully bleached pulp by about I ISO% point. This can apparently reduce the amount of the chemicals used in the bleaching process. The results on the sugar analysis of the pulps showed that in terms of carbohydrate composition, there were no significant differences between the bio-treated and control pulps. However, the strength properties of the un-bleached and bleached chemical straw pulps decreased slightly after the fungal pretreatment. This is different from reported results that the strength properties of mechanical pulps were improved after the fungal pre-treatment. There was no difference of the two while-rot fungal species, Ceriporiopsis subvesmispora and Phlebia subserialis in term of their effect on the strength properties.